Analisis Strategi SDM dalam Penguatan Kerja Sama Tim pada Perusahaan Distribusi Ikan Asin “Marta Jambal” di Kabupaten Pangandaran - Clara Rahma Dewi; Maya R Atmawinata (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to examine the implementation of human resources (HR) strategies to strengthen team collaboration at the Marta Jambal salted fish distribution company located in Pangandaran Regency. Team collaboration is a crucial element in supporting operational efficiency, particularly in the distribution sector, which demands high coordination among team members. To achieve this objective, this study employed a qualitative descriptive approach with data collection methods including in-depth interviews, direct observation of operational activities, and company documentation studies. The results indicate that the company implements a comprehensive and contextual HR strategy. This strategy includes the integration of local wisdom values, which serve as the basis for building closeness and mutual trust among employees. Furthermore, the company implements training programs tailored to the work needs of each department to improve individual competencies and team effectiveness. Another prominent aspect is the clarity of roles and responsibilities, which are systematically established, thereby reducing overlapping tasks and accelerating work processes. Open and transparent communication patterns also serve as an important foundation in creating a work environment that supports collaboration. The combination of these strategies has been proven to create strong team synergy and a solid work culture within the company. Based on these findings, this study recommends that companies regularly update and evaluate their implemented HR strategies. Furthermore, strengthening a collectivist work culture also needs to be continuously improved to ensure the sustainability of effective collaboration in the future.